Are neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and/or mean platelet volume (MPV) clinically useful as predictive parameters for preeclampsia?. (3rd May 2019) - Mannaerts, Dominique; Heyvaert, Suzanne; De Cordt, Chania; Macken, Claartje; Loos, Charlotte; Jacquemyn, Yves
Abstract: Objective: Preeclampsia (PE) is a severe pregnancy complication with significant maternal and neonatal morbi–mortality resulting in high health care costs. Prevention, mainly based on the administration of acetylsalicylic acid, is only possible if timely identification of high-risk patients can be realized in an easy, nonexpensive, and widely available method. This paper explores the clinical usability of neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and/or mean platelet volume (MPV) in discriminating between women that will and those that will not develop PE. Study design: Demographic data and laboratory results were retrospectively collected and compared in 2050 pregnant women (164 PE and 1886 controls) between 1 January 2014 and 31 January 2016. Results: In the PE group, gravidity, parity, gestational age, and birth weight were significantly lower compared to the control group. Before the 20th pregnancy week, MPV was significantly elevated in the PE group compared to the controls ( p  = .006), hence analysis revealed an optimal cut-off point of 8.15 (sensitivity 66.7%, specificity 56.3%) for predicting PE. At the end of pregnancy, NLR and MPV appeared to be higher and PLR lower in the PE group compared to the controls, which strengthens the current knowledge on the pathogenesis of PE. Conclusions: MPV is significantly elevated in the first half of pregnancy in women who later develop PE and might therefore be implemented in combination with other parameters in a PE prediction model.